Hydrochemical Characterization of Lentic and Lotic Environments of Ramaroshan Area, Sudurpaschim Province, Nepal - Pant, Ramesh Raj; Dangol, Alina; Chalaune, Tarka Bahadur; Sharma, Jiban; Thapa, Bina; Thapa, Lal B.; Bishwakarma, Kiran (Geographical Journal of Nepal, 2022)
Ramaroshan of Sudurpaschim Province is rich in biodiversity, and ecologically distinct but scientifically unexplored rural and remote area of Nepal. There is a holy perennial Kailash River as a lentic and aesthetically well-known Ramarosan Lake Cluster (Batula Lake) as a lotic environment located in the region. This study has analyzed and then characterized the water quality status of both the lentic and lotic environments. The physicochemical parameters such as temperature, pH, electrical conductivity (EC), total dissolved solids (TDS), and major ions were analyzed for the hydrochemical characterization. The results revealed that the dominancy orders of cations and anions of the study area were found to be Ca2+ > Na+ >Mg2+ > K+ > NH4+ and HCO3- > Cl- > SO42- > PO43- > NO3-, respectively. The concentrations of most of the parameters were relatively higher in the Kailash River than the Batula Lake except for the SO42-, PO43- and NH4+. The water facies displayed the Ca-HCO3 type indicating the calcium carbonate type of lithology in the area. Additionally, the carbonate weathering is also higher than the silicates and evaporates. Similarly, the source controlling mechanisms indicated that the hydrochemistry of the Ramaroshan area is determined by both geogenic weathering and precipitation. Water quality assessment for irrigation parameters confirmed its suitability for irrigational purposes. The finding of this study could be the baseline dataset for assessing the future status and management of water resources of the Ramaroshan area.